2021
DOI: 10.3390/biomedicines9030251
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Is Differentially Modulated by Platelet-Derived Products

Abstract: Platelet-derived preparations are being used in clinic for their role in tissue repair and regenerative processes. The release of platelet-derived products such as autologous growth factors, cytokines and chemokines can trigger therapeutic angiogenesis. In this in vitro study, we evaluated and compared the ability of three platelet-derived preparations: platelet-rich-plasma (PRP), PRP-hyaluronic acid (PRP-HA) and platelet lysates (PL) at various concentrations (5–40%) to modulate human umbilical vein endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…This result further confirmed the advantage previously observed when incorporating PRP within GelMA to increase scaffold vascularisation and angiogenic potential. Our results corroborate other literature reports highlighting the pro‐angiogenic aspects of PRP, [ 13–17 ] however, it is highly encouraging that we have now also shown that these properties are fully retained after PRP was utilized in the novel biofabrication process developed in this study. Despite this compelling evidence of the pro‐angiogenic potential of our PRP‐GelMA scaffolds, we acknowledge that future in vivo analysis, such as subcutaneous implantation in a mammalian model, might be needed to better evaluate the scaffolds’ regenerative potential and to understand the host immune response to the implanted materials.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result further confirmed the advantage previously observed when incorporating PRP within GelMA to increase scaffold vascularisation and angiogenic potential. Our results corroborate other literature reports highlighting the pro‐angiogenic aspects of PRP, [ 13–17 ] however, it is highly encouraging that we have now also shown that these properties are fully retained after PRP was utilized in the novel biofabrication process developed in this study. Despite this compelling evidence of the pro‐angiogenic potential of our PRP‐GelMA scaffolds, we acknowledge that future in vivo analysis, such as subcutaneous implantation in a mammalian model, might be needed to better evaluate the scaffolds’ regenerative potential and to understand the host immune response to the implanted materials.…”
Section: Resultssupporting
confidence: 91%
“…PRP is an autologous source of growth factors that play important role in skin wound healing, [ 11 ] particularly in angiogenesis and vascularization, with specific components including vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), and platelet‐derived growth factor (PDGF). [ 12 ] Several reports have already shown evidence of PRP's pro‐angiogenic potential, [ 13–17 ] supporting its use for wound healing in a clinical scenario. [ 18,19 ] However, despite its pro‐angiogenic effects, the bulk and direct use of PRP on its own carries a risk of inducing fibrosis in the skin [ 20,21 ] and should be taken into careful consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical proteomic studies performed on some PRP products have demonstrated that the cellular activities performed by the various platelet constituents within the storage granules play an important role in maintaining most basic cell functions by acting as endocrine, paracrine, autocrine, and intracrine mediators [44,45]. Several studies have indicated the potential of platelets and PRP in angiogenesis by enhancing EC proliferation, migration, and tube formation [46,47].…”
Section: Prp In Tissue Repair Mechanismsmentioning
confidence: 99%
“…The release of platelet-derived products, such as autologous growth factors, cytokines and chemokines, can trigger therapeutic angiogenesis. In an in vitro study, we evaluated and compared the ability of three platelet-derived preparations: plateletrich-plasma (PRP), PRP hyaluronic acid (PRP-HA) and platelet lysates (PL) at various concentrations (5-40%) to modulate human umbilical vein endothelial cells' (HUVECs') biological effects on metabolism, viability, senescence, angiogenic factors secretion and angiogenic capacities in 2D (endothelial tube formation assay or EFTA) and in 3D (fibrin bead assay or FBA) [84].…”
Section: Angiogenesis Is Differentially Modulated By Platelet-derived...mentioning
confidence: 99%
“…CM-PRP-HA also stimulated angiogenesis but to a lesser extent than PRP: this could be explained as being due to the concentration of platelets in this preparation being reduced by half in comparison to PRP. Platelet lysates had to be highly concentrated to elicit the same angiogenic response as PRP and CM-PRP-HA [84]. -…”
Section: Angiogenesis Is Differentially Modulated By Platelet-derived...mentioning
confidence: 99%